The Correlation between Perception on Dormitory Food and Nutrient Intake of Young Athletes Residing at Athlete’s Dormitory - Rais, Anggy Shazia; Setyowati, Setyowati; Palupi, Ika Ratna (Unnes Journal of Public Health, 2019)
Young athletes who go to training centers under the Department of Youth and Sport may fulfill their dietary needs from meals provided in the accommodation facilities, yet they can also access foods outside the dormitories. Perception on institutional food can influence one’s food intake and nutritional adequacy. This study used cross-sectional design and involved 24 athletes of martial sports from Student Education and Training Center (PPLP) Central Java Indonesia who resided in Jatidiri athlete’s hostel Semarang. Variables were measured using questionnaire, food record form, and body weight measurement whereas data were analyzed using Pearson and Spearman correlation test. Perception on dormitory foods had no correlation with intake of energy, macronutrient, vitamin C, and calcium from dormitory food (p>0.05) but it had significant correlation with intake of energy, protein, and fat from meals outside the dormitory (p<0.05). Menu improvement is proposed to increase the intake of dormitory meals.